Keterlibatan keluarga dalam upaya pencegahan dekubitus pada pasien defisit neurologis - Surjati Dihardjo, Christantie E dan Haryani (Berita Kedokteran Masyarakat (BKM), 2005)
Background: Decubitus is a serious problem in family health. In addition to make the care period longer and make the cost more expensive, it also decelerates the rehabilitation program for the victim. Therefore, the preventive action needs to be conducted, among others, by involving the family of patient. The familial involvement in preventing decubitus can enhance their knowledge on decubitus, also they can learn in caring and assisting the patient of the neurological deficit so that the patient does not suffer from decubitus. Objectives: To find out the familial involvement in preventing decubitus for patient of the neurological deficit at Dahlia room in Dr. Sardjito Hospital Yogyakarta. Methods: The study is the explorative descriptive research and it is cross sectional in model. The research was conducted in December 27th 2004 January 10th 2005 at Dahlia room in Dr. Sardjito Hospital,and its respondents were 25 people. Data gathering was done by observation. Data processing was accomplished by evaluating the total score that was acquired by each respondent. Results: From 12 items that were observed, those who acquire > 75% in score or "very good" in classification are 5 respondents (20%). Respondents who gain 56-15% in scores or "good' in classification are 13 respondents (52%). Respondents who gain 40-55% in scores or "bad" in classification are 5% (20%) and respondents who gain